Single-cell RNA sequencing of Plasmodium vivax sporozoites reveals stage- and species-specific transcriptomic signatures. - Anthony A Ruberto; Caitlin Bourke; Amélie Vantaux; Steven P Maher; Aaron Jex; Benoit Witkowski; Georges Snounou; Ivo Mueller (Public Library of Science (PLoS), 2022)
Background Plasmodium vivax sporozoites reside in the salivary glands of a mosquito before infecting a human host and causing malaria. Previous transcriptome-wide studies in populations of these parasite forms were limited in their ability to elucidate cell-to-cell variation, thereby masking cellular states potentially important in understanding malaria transmission outcomes. Methodology/principal findings In this study, we performed transcription profiling on 9,947 P. vivax sporozoites to assess the extent to which they differ at single-cell resolution. We show that sporozoites residing in the mosquito's salivary glands exist in distinct developmental states, as defined by their transcriptomic signatures. Additionally, relative to P. falciparum, P. vivax displays overlapping and unique gene usage patterns, highlighting conserved and species-specific gene programs. Notably, distinguishing P. vivax from P. falciparum were a subset of P. vivax sporozoites expressing genes associated with translational regulation and repression. Finally, our comparison of single-cell transcriptomic data from P. vivax sporozoite and erythrocytic forms reveals gene usage patterns unique to sporozoites. Conclusions/significance In defining the transcriptomic signatures of individual P. vivax sporozoites, our work provides new insights into the factors driving their developmental trajectory and lays the groundwork for a more comprehensive P. vivax cell atlas.